PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 023 SEDINGINAN KECAMATAN TANAH PUTIH - Sri Kartika Eka Wati; Munjiatun '; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by lack of science learning outcomes of student with an average of 58,75. This from of research is Classroom Action Research (CAR) which consists of two cycles that implementation began on on march 24, 2015 to April 14, 2015 with the subject at 20 students. This study aims to improve science learning out comes grade IV elementary school 023 Sedinginan thourghthe implementation of cooperatife learning model Contextual Teaching And Learning (CTL) The research instruments consists of learning tools and data on the collection intrumens. The data analysis technique the used is the analysis of the observation sheets and student learning outcomes. Mechanical analysis of data on the activities of teachers and student based on the observation sheet for the implementation of the action. While the analysis of student learning outcomes data demonstrate mastery of student learning outcomes. The frequency distribution for the highest valueof the range and infroving students learning outcomes. Based on the analysis of the observations sheet activities of teachr and students saw an increase include : teacher activity in the fisr cycle reaches 58,3 %, 70,8 % whereas the activity of students in the first cycle reaches 83,3 %, 95,8 %. Analysis of the data showed an increase in student learning outcomes are: mastery learning students 79,2 % in the first cycle, second cycle and third second 91,7 %, the frequency distribution for the highest range of value for each cycle increase, this show that the applications of cooperatif learning model to improve learning outcomes Contextual Teaching And Learning (CTL) IPA fourth grade IV Direct Instruction students SD Negeri 023 Sedinginan.Key Words: Model Contextual Teaching And Learning (CTL), learning outcomes IPA.